Relationship Between Mother's Knowledge Level on Monitoring Behavior of Toddler Growth and Development at Gunung Alam Public Health Center, Arga Makmur City District, North Bengkulu Regency - Dwi Hermawati (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
A good knowledge of mother will influence the behavior of observing the growth and development of the under five year’s old children, so that the children achieve an optimal growth and development. The aim of the research is to know the relation between mother’s knowledge toward the behavior of observing growth and development of fewer than five years old children at the Gunung Alam health centre in the area of Argamakmur. The design of the research is Analytic Survey with Cross Sectional approach. The population of the research is 300 mothers and the sample was taken Randomly (Simple Random Sampling) the result got 171 sample by using Corelative Product Moment Statistic. The result of unvaried analysis at the stage of knowledge shows 56 mothers (32,7%) have moderate knowledge. The distribution of the behavior of observing growth and development of under five years old children mostly ‘sometimes’ behavior 87 (50,9%). Bivariat analysis with the result of correlative product moment test (r test) with a 0,05 and CL 95% shows that all independent variabele; mother’s knowledge and dependent _ariable that is behavior of observing growth and development under five years old children shows that they have positive relation and significant 0,606 with a 0,05 its got ro = 0,606 and t test got 9,892. Since r account higher than r table (0,148), thus behavior of observing growth and development under five years old children. The category of the relation is significant (moderate relation). It can be concluded that the higher mother’s knowledge, the higher mother’s in observing the growth and development of the under five years old children.